2D Hexagonal Boron Nitride/Cadmium Sulfide Heterostructure as a Promising Water‐Splitting Photocatalyst. Issue 1 (8th October 2019) - Wang, Guangzhao; Zhi, Yan; Bo, Maolin; Xiao, Shuyuan; Li, Yue; Zhao, Wenxi; Li, Yadong; Li, Yang; He, Zelong
Abstract : This research calculates the structural, optical, and electronic properties of original and strained hexagonal boron nitride/cadmium sulfide (h‐BN/CdS) heterostructures using a hybrid density functional method. The electron transfer from CdS to h‐BN sheet leads to the formation of electric field across the interface, which is beneficial for efficient separation of electron–hole pairs. The bandgaps of heterostructures decrease with the increase in the strain. In addition, biaxial strain can obviously tune the bandgaps and band alignments of h‐BN/CdS heterostructures. The heterostructures in the strain range from 0% to 6% possess suitable bandgaps for visible light utilization and appropriate band alignments for spontaneous production of hydrogen and oxygen. Especially, the original, −2% strained, and 2% strained h‐BN/CdS heterostructures can be easy to form due to the negative interface formation energy. The original and 2% strained h‐BN/CdS heterostructures are potential candidates as water‐splitting photocatalysts. Abstract : Negative interface formation energies for experimental preparation, suitable bandgaps for visible light utilization, and appropriate band alignments for spontaneous production of hydrogen and oxygen make the original and 2% strained hexagonal boron nitride/cadmium sulfide (h‐BN/CdS) heterostructures potential water‐splitting photocatalysts.